Pengembangan Kompetensi Sumber Daya Manusia untuk Mencapai Career Ready Professional di Universitas Tanri Abeng - Ahmad Azmy (Bina Nusantara University, 2015)
This article discusses the development of competence in achieving organizational goals. This research discusses how the competence development of human resources in achieving the organization's motto, that is Career Ready Proffesional in Tanri Abeng University. This research objective is to analyze the organization's role in developing the human resource competencies in achieving organizational goals. The method used is descriptive. This research compared the theories related to the topic of research with applications that have been carried out and reinforced by previous studies. The results showed that development of human resource competencies needs to be done in achieving organizational goals. Organizational development and change must be done simultaneously and measured the results within a certain time. Both processes require competencies that are required by all members of the organization. Increased competence can be done by providing the process of knowledge transfer between members of the organization. The key of success is the commitment and communication.